PERBANDINGAN PRODUKSI BIOGAS MENGGUNAKAN SUMBER MIKROBA DARI KOTORAN SAPI DAN KOTORAN AYAM DENGAN BAHAN BAKU LIMBAH CAIR INDUSTRI TAHU ( The Comparation of Biogass Production Using Cow Dung and Chicken Manure With Tofu Industrial Wastewater As Raw Mater - Panisean Nasoetion; Natalina _; Hardoyo _; Tri Minsrto (IST AKPRIND Yogyakarta, 2018)
The tofu industry is one of the processing industries, that produced wastewater countain many organic matter. Those organic matters could be decomposed by biological process. One of the treatment of those wastewater was anaerobically fermentation to produce biogas. The anaerobic fermentation depend of the use of starter, like cow dung and chicken manure. The purpose of this research was to know the comparation biogas production using cow dung and chicken manure from tofu industrial wastewater. The research was used on the 15 liter continuously-anaerobic bioreactor with 15 days retention time. The influen were added 2 liter/2days continuously. The tested variable were COD and biogas composition.The research result showed that the COD in the tofu wastewater were reduced from 10.400- 10.700 mg/l in the influent to 2.400-2.700 mg/l and 2850-3500 mg/l in the effluent for cow dung stater and chicken manure stater. The CH4 concentration in the produced biogas were 40,73 % and 25,71 % for cow dung stater and chicken manurestater. The cow dung was better than chicken manure that used as stater on the degradation organic material in the tofu industrial wastewater to produce biogas. That cause cow dung contain some bacteria like methanogenese microbe, while chicken manure did not contain that bacteria. The mthanogenesis bacteria were actively bacteria to degarade organic matter to produce biogas anaerobically